Non-structural carbohydrate and water dynamics of Moso bamboo during its explosive growth period - Li, Xue; Ye, Chongyu; Fang, Dongming; Zeng, Qiangfa; Cai, Yanjiang; Du, Huaqiang; Mei, Tingting; Zhou, Guomo (Frontiers in Forests and Global Change, 2022)
Newly sprouted culm (culm_new) of Moso bamboo can complete its height growth within one or two months without growing any leaf. This explosive growth without leaf photosynthesis may rely heavily on external carbon input, such as carbon storage in the rhizomes or culms from the nearby mother culms (culm_mother). However, the existing studies have not explored the role of newly photosynthesis carbon by the nearby culm_mother and the corresponding water dynamics. Therefore, this study monitored nonstructural carbohydrates in the culm_mother and water transfer between the culm_new and their attached culm_mother in a three-month experiment. Nine pairs of newly sprouted and attached culm_mother were categorized into three groups with three different treatments, i.e., 1) control without any treatment, 2) cutting off rhizomes between the culm_new and culm_mother (Treatment I), 3) removing all leaves of culm_mother based on the Treatment I (Treatment II). The difference between nonstructural carbohydrates of the culm_mother in the control and treatment I was defined as transferred carbohydrates transferred outward from culm_mother. The difference between treatments I and II was defined as newly photosynthesized carbohydrates of the culm_mother. Before the culm_new leafing, there was significant transferred carbon and newly photosynthesis carbon from the culm_mother. In contrast, the carbon transfer became fewer after leafing. At the same time, the sap flow direction in the rhizomes indicated water flows from culm_new to culm_mother during the day and vice versa at night of the culm_new at the pre-leafing stage. These findings suggest that the explosive growth of the culm_new relies on both previous carbon storage and newly photosynthesized carbohydrates, and the carbon transfer may be coordinated with water transportation between the culms. Further study may pay attention to the potential support from the overall network of the bamboo stand or groves.